2006
DOI: 10.4049/jimmunol.177.5.3218
|View full text |Cite
|
Sign up to set email alerts
|

IL-12, but Not IL-18, Is Critical to Neutrophil Activation and Resistance to Polymicrobial Sepsis Induced by Cecal Ligation and Puncture

Abstract: Sepsis is a systemic inflammatory response resulting from local infection due, at least in part, to impaired neutrophil migration. IL-12 and IL-18 play an important role in neutrophil migration. We have investigated the mechanism and relative role of IL-12 and IL-18 in polymicrobial sepsis induced by cecal ligation and puncture (CLP) in mice. Wild-type (WT) and IL-18−/− mice were resistant to sublethal CLP (SL-CLP) sepsis. In contrast, IL-12−/− mice were susceptible to SL-CLP sepsis with high bacteria load in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 56 publications
4
63
1
1
Order By: Relevance
“…1A), indicating that endogenous IL-18 plays a critical adverse role in neonatal sepsis. This finding in neonates is in stark contrast to the absence of any effect of IL-18 deletion alone in adults after polymicrobial sepsis induced by cecal ligation and puncture (CLP) (12). Of note, sepsis modeling using cecal slurry (CS) results in a much more robust early systemic inflammatory response than seen with CLP; this robust response may contribute to the differences in survival seen between IL-18 −/− neonates and adults (13).…”
Section: Resultscontrasting
confidence: 52%
“…1A), indicating that endogenous IL-18 plays a critical adverse role in neonatal sepsis. This finding in neonates is in stark contrast to the absence of any effect of IL-18 deletion alone in adults after polymicrobial sepsis induced by cecal ligation and puncture (CLP) (12). Of note, sepsis modeling using cecal slurry (CS) results in a much more robust early systemic inflammatory response than seen with CLP; this robust response may contribute to the differences in survival seen between IL-18 −/− neonates and adults (13).…”
Section: Resultscontrasting
confidence: 52%
“…Although being dispensable for the recruitment of neutrophils in our as well as other model systems (65), IFN-␥ is known to induce neutrophil phagocytosis (66), microbicidal activity (67), and survival (68). We propose that CD4 ϩ T cell-derived IFN-␥ must act locally on neutrophils to activate their anti-Helicobacter properties.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 has been demonstrated to be chemotactic for neutrophils and NK cells through induction of synthesis of platelet-activating factor (44,45). It also has been reported that IL-12 is critical to neutrophil activation and resistance to polymicrobial sepsis induced by cecal ligation and puncture (46). Therefore, vaccine-induced specific antibodies blocked the biophysical functions of IL-12, leading to less migration and activation of neutrophils to the local colon tissue and, thus, ameliorating intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%